Splicing inhibition induces gene expression through canonical NF‐κB pathway and extracellular signal‐related kinase activation. Issue 6 (20th February 2014) - Khan, Khalid; Schneider-Poetsch, Tilman; Ishfaq, Muhammad; Ito, Akihiro; Yoshimoto, Rei; Mukaida, Naofumi; Yoshida, Minoru
Abstract : Splicing, a process for mRNA maturation, is essential for correct gene expression after transcription. However, recent studies also suggest that splicing affects transcription, but its mechanism remains elusive. We previously reported that treatment with spliceostatin A (SSA), a specific splicing inhibitor targeting the splicing factor SF3b, leads to transcriptional activation of a small subset of genes. To investigate the underlying mechanism we utilized luciferase reporters driven by the Interleukin 8 (IL‐8) and cytomegalovirus (CMV) promoters, as both recruit a similar set of transcription factors. We also found that SSA treatment led to increased extracellular signal‐regulated protein kinase (ERK) activity and that chemical inhibition of ERK also led to decreased promoter activation. Systematic deletion studies suggested that NF‐κB activation is mainly responsible for SSA‐induced promoters activation. Abstract : SSA enhances gene expression through NF‐κB and ERK pathway. Parthenolide and PD98059 inhibit SSA‐induced CMV and IL‐8 stimulation. SSA affects IκBα degradation and nuclear localization of NF‐κB‐p65.